Determinants of eHealth Literacy among Adults in China. Issue 5 (3rd May 2020) - Lwin, May Oo; Panchapakesan, Chitra; Sheldenkar, Anita; Calvert, Gemma Anne; Lim, Lewis K.S.; Lu, Jiahui
Abstract : eHealth can empower patients to make informed health decisions. However, inaccurate and misleading health information is not uncommon on the Internet, which requires users' competencies to both utilize eHealth technologies and evaluate eHealth credibilities. Therefore, this study investigates the determinants of both self-efficacy in utilizing eHealth and frequency of eHealth information evaluation. An Internet-based survey of 923 Chinese adults who are residing in China aged from 21 to 55 years old was conducted. Path analysis was adopted to examine sociodemographic variables, Internet literacy, and health information evaluation as determinants of eHealth literacy variables. Findings demonstrated that Internet literacy positively predicted only self-efficacy in utilizing eHealth. In contrast, health information orientation positively predicted both self-efficacy in utilizing eHealth and frequency of eHealth information evaluation. In addition, Internet literacy and health information orientation mediated the predicted effects of sociodemographic factors on the two eHealth variables. The findings imply that Internet literacy is no longer the primary determinant of eHealth competencies for adults who are tech-savvy users. Instead, interests in health information play a crucial role in improving eHealth competencies.